Annual reproductive cycle of males of the bat Molossus molossus: Seasonal bimodal polyestry, testicular regression, and some aspects of the hormonal control - Soares, Emília M.; Ferraz, Juliana F.; Oliveira, Rodrigo S.; Dias, Luíza I.S.; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastião R. [UNESP]; Souza, Carolina C.; Beguelini, Mateus R. (Elsevier, 2020)
Bats are mammals that play a fundamental role in the regulation of the ecosystems by, for example, controlling the insect populations. Therefore, insectivorous species, such as Molossus molossus, have become the target of great scientific interest. Despite the different studies that exist on the species, there is still no consensus regarding its reproduction. Thus, this study aimed to analyze the morphophysiology and some aspects of the hormonal control of the testes of M. molossus (Chiroptera: Molossidae), by evaluating its morphological and morphometric variations throughout the annual reproductive cycle. Sixty sexually adult males of M. molossus were used in the study, with five specimens collected each month for one year, forming 12 sample groups. The testes of each bat were submitted to morphological, morphometric, and immunohistochemical analyses. Molossus molossus presented an annual reproductive cycle with two peaks of spermatogenic activity, one in April and the other in September, and a period of total testicular regression in December, which has never been described. The cycle appeared to be regulated by rainfall and was, at least partially, controlled by the expression of the androgen receptor in Sertoli cells, which has agonist effects on cell proliferation.
Keywords: Reproduction; Seasonality; Testicular regression; Testis